War Matador - Faingulernt, Avner; Abramson, Macabit (Israel : Independance Film Makers, 2011)
Shot during Operation Cast Lead, a three-week bombing of the Gaza Strip in 2009 by Israel, the film juxtaposes bombing footage, shot out of focus and at extreme focal length, with blunt commentary by onlookers. The interviews are with the people living in the area along the Gaza–Israel border as well as the “gawkers” – those coming from all over the country, and some even beyond, to observe the events.
Verzio Film Festival Submission
Duration: 01:02:00
Verzio Film Festival Submission
Keywords: Documentary films